Harnessing Chat GPT (generative pretrained transformer) to engage youth and women in climate-smart and sustainable livestock farming - Ekule, Muluken; Rudiger, Udo (All Africa Conference of Animal Agriculture, 2023)
This literature review on harnessing Chat GPT focusses on how Chat GPT guides youth and women on feed production. least cost formulation, forecasting feed balance. It highlights advances, gaps and opportunities in literature.